ALS Yeast Models—Past Success Stories and New Opportunities - Di Gregorio, Sonja E.; Duennwald, Martin L. (Frontiers in Molecular Neuroscience, 2018)
In the past two decades, yeast models have delivered profound insights into basic mechanisms of protein misfolding and the dysfunction of key cellular pathways associated with ALS (amyotrophic lateral sclerosis). Expressing ALS-associated proteins in yeast recapitulates major hallmarks of ALS pathology, including protein aggregation and mislocalization. Of note, ALS yeast models have revealed both protein-specific and more general features of ALS pathogenesis. Results from yeast have consistently been validated in other model systems and specimens from human patients. Here we summarize exemplary discoveries that originated from work in yeast and propose experimental strategies that will continue to decipher the basic pathomechanisms underlying ALS and thus possibly contribute to finding a cure.